Do we need to measure progesterone in oocyte donation cycles? A retrospective analysis evaluating cumulative live birth rates and embryo quality. Issue 1 (18th January 2020) - Racca, A; De Munck, N; Santos-Ribeiro, S; Drakopoulos, P; Errazuriz, J; Galvao, A; Popovic, B; Mackens, S; De Vos, M; Verheyen, G; Tournaye, H; Blockeel, C
Abstract: STUDY QUESTION: Does late follicular-phase elevated serum progesterone (LFEP) during ovarian stimulation for oocyte donation have an impact on embryo quality (EQ) and cumulative live birth rate (CLBR)? SUMMARY ANSWER: LFEP does not have an influence on EQ nor CLBR in oocyte donation cycles. WHAT IS KNOWN ALREADY: Ovarian stimulation promotes the production of progesterone (P) which, when elevated during the follicular phase, has been demonstrated to have a deleterious effect in autologous fresh IVF outcomes. While there is robust evidence that this elevation results in impaired endometrial receptivity, the impact on EQ remains a matter of debate. The oocyte donation model is an excellent tool to assess the effects of LFEP on EQ from those on endometrium receptivity separately. Previous studies in oocyte donation cycles investigating the influence of elevated P on pregnancy outcomes in oocyte recipients showed conflicting results. STUDY DESIGN, SIZE, DURATION: This is a retrospective analysis including all GnRH antagonist down-regulated cycles for fresh oocyte donation taking place in a tertiary referral university hospital between 2010 and 2017. A total of 397 fresh donor-recipient cycles were included. Each donor was included only once in the analysis and could be associated to a single recipient. PARTICIPANTS/MATERIALS, SETTING, METHODS: The sample was stratified according to serum P levels of ≤1.5 and >1.5 ng/mL on the day of ovulation triggering. The primary endpoint of the study was the top-quality embryo rate on Day 3, and the secondary outcome measure was CLBR defined as a live-born delivery beyond 24 weeks. MAIN RESULTS AND THE ROLE OF CHANCE: Three hundred ninety-seven fresh oocyte donation cycles were included in the analysis, of which 314 (79%) had a serum P ≤ 1.5 ng/mL and 83 (20.9%) had a serum P > 1.5 ng/mL. The average age of the oocyte donors was 31.4 ± 4.7 and 29.9 ± 4.5 years, respectively, for normal and elevated P ( P  = 0.017) . The mean number of oocytes retrieved was significantly higher in the elevated P group with 16.6 ± 10.6 vs 11.5 ± 6.9 in the P ≤ 1.5 group ( P  < 0.001). In parallel, the total number of embryos on Day 3, as well as the number of good-quality embryos at this stage, was significantly higher in the elevated P group (6.6 ± 5.6 vs 4.15 ± 3.5 and 8.7 ± 6.3 vs 6.1 ± 4.4; respectively, P  < 0.001). However, maturation and fertilization rates did not vary significantly between the two study groups and neither did the top- and good-quality embryo rate and the embryo utilization rate, all evaluated on Day 3 ( P  = 0.384, P  = 0.405 and P  = 0.645, respectively). A multivariable regression analysis accounting for P groups, age of the donor, number of retrieved oocytes and top-quality embryo rate as potential confounders showed that LFEP negatively influenced neither the top-quality embryo rate nor the CLBR. LIMITATIONS, REASONS FOR CAUTION: This is an observational study based on a retrospective data analysis. Better extrapolation of the results could be validated by performing a prospective trial. Furthermore, this study was focused on oocyte donation cycles and hence the results cannot be generalized to the entire infertile population. WIDER IMPLICATIONS OF THE FINDINGS: This is the first study providing evidence that LFEP does not influence CLBR and is adding strong evidence to the existing literature that LFEP does not harm EQ in oocyte donation programs. STUDY FUNDING/COMPETING INTERESTS: Not applicable.